Crosslinks Between Human Leukocyte Antigen DRB1*01 and Human Leukocyte Antigen DRB1*13 Allelic Variants and Occurrence of Rheumatoid Arthritis in Patients From Federation of Bosnia and Herzegovina - Elma FEJZIC,; Amela SAHOVIC,; Sanela SISIC,; Andi ALIJAGIC,; Damir SULJEVIC, (Archives of Rheumatology, 2017)
Objectives: This study aims to analyze human leukocyte antigen A (HLA-A), human leukocyte antigen B (HLA-B), human leukocyte antigen C (HLA-C), HLA-DRB1*, HLA-DRB3*, HLA-DRB4*, HLA-DRB5*, HLA-DQB1* loci expression in patients with rheumatoid arthritis (RA) in the Federation of Bosnia and Herzegovina. Patients and methods: Deoxyribonucleic acid was isolated from peripheral blood of 48 RA patients (22 males, 26 females; mean age 36 years; range 2 to 63 years) and 104 healthy control individuals (52 males, 52 females; mean age 43 years; range 2 to 76 years). Deoxyribonucleic acid samples were analyzed using polymerase chain reaction-sequence-specific primers and sequence specific oligonucleotides methods. Results: The most frequent allelic groups in RA patients were HLA-DRB1*01 (odds ratio=2.795; 95% confidence interval: 1.441-5.421; p=0.004) and HLA-DRB1*04 (odds ratio=2.573; 95% confidence interval: 1.214-5.453; p=0.023). Among RA patients, the most frequent genotype for the allelic group HLA-DRB1*, in the light of the common epitopes theory, was observed for DRB1*01/DRB1*13. This genotype indicates an increased incidence and relative risk (odds ratio=11.09). Conclusion: The most common genotype in our RA patients was DRB1*01/DRB1*13, which showed increased frequency and a high relative risk. This genotype variant may be considered a predisposing factor for the development of RA.